2021
DOI: 10.1038/s41598-021-81521-z
|View full text |Cite|
|
Sign up to set email alerts
|

Self-organized wavy infection curve of COVID-19

Abstract: Exploiting the SIQR model for COVID-19, I show that the wavy infection curve in Japan is the result of fluctuation of policy on isolation measure imposed by the government and obeyed by citizens. Assuming the infection coefficient be a two-valued function of the number of daily confirmed new cases, I show that when the removal rate of infected individuals is between these two values, the wavy infection curve is self-organized. On the basis of the infection curve, I classify the outbreak of COVID-19 into five t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…1 we exhibit the fractions of Susceptible, Infected, Recovered and Dead individuals for the three areas 1, 2 and 3 as functions of time for C 1 = 1.0, C 2 = 0.4 and C 3 = 1.3, obtained from the numerical integration of Eqs. ( 5) - (8). Since the exposure coefficients are arbitrary parameters, we chose as unity the one for government controlled areas and modified the other two accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…1 we exhibit the fractions of Susceptible, Infected, Recovered and Dead individuals for the three areas 1, 2 and 3 as functions of time for C 1 = 1.0, C 2 = 0.4 and C 3 = 1.3, obtained from the numerical integration of Eqs. ( 5) - (8). Since the exposure coefficients are arbitrary parameters, we chose as unity the one for government controlled areas and modified the other two accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…The policy targeting on certain shops and opening hours has only limited effects on social distancing since people gather together in a park or on a street. Furthermore, the policy has been enforced and lifted every one or two months, which has caused the wavy infection curve (9,10). It could be possible to increase by, for example, promoting Telework, limiting working days, reducing crowd in commuter trains and banning gatherings.…”
Section: Effective Reproduction Number and Assessment Of Policiesmentioning
confidence: 99%
“…The SIQR model [10,11] separates quarantined patients (Q) as a compartment in the population and α in Eq. ( 1) is given by the quarantine rate q ≡ ∆Q(t)/I(t) where ∆Q(t) is the daily confirmed new cases [7]. In the application of the SIQR model to COVID-19, it has been shown that…”
Section: Model Countrymentioning
confidence: 99%